Can entanglement explain black hole entropy? - Ried, Katja [UNESP] (2010)
When seeking inspiration for a future theory of quantum gravity, studying black holes is a promising ansatz, since they present us with several puzzles at the intersection of quantum theory and gravity. Among these is their entropy: although there are compelling arguments for its existence, its origin and statistical meaning remain a mystery. Previous work showed that at least some aspects of this phenomenon can be accounted for by the entanglement of quantum fields across the horizon: if a field is globally in a pure state, yet part of it is hidden behind the event horizon, then the reduced state of the remainder possesses non-zero entropy. This is the possibility we explore in the present work, in the simplest of settings: a ground-state escalar field, defined in three-dimensional, flat or unifromily curved space, and derive an expression for the entropy, which is evauated numerically. the results show that the entropy scales with the boundary area of the inaccessible region, a key feature of black hole entropy known as the area law. Furthermore. we conclude that the dominant contribution to the entropy is due to short-range interactions, and discuss some physical implications of this insight for the puzzle of black hole entropy